Corpo e escrita: linhas e entrelinhas da produção de conhecimento em sala de aula - Souza, Ana Cleide Silva de (2008)
Body and writing: Lines and between-lines of production of knowledge in the classroom it is an ethnographic research, longitudinal character, based on experience while experienced educator of the Escola Municipal Professor Amadeu Araújo, located in the city of Natal-RN, from which are made reflections about texts written by students who have distorted age/education level, in the process of literacy. Here as initial goal: to discuss the production of students writing as a process body, considering the record of experiences and the impressions they have made during the teaching process. We initially by a conception of phenomenological body, by understanding it in its complexity, a phenomenon that is made from its relationship with the world and with the Other. The records examined were produced between the year 2000 and 2005 involving writings of 106 students, constituting a universe of 136 texts, from which, delimited a corpus of 27 texts. The relevance with respect to the theme and recurrence in which they were detected, were up to elements that allowed a systematization methodology, defining the following units of analysis: Body, written in everyday; body, written and sexuality; body, written and enjoyment poetics; body, writing and other stories. We used the techniques of search, participant observation, based on the actions and interactions body expressed during the experiment and the analysis of documents that consisted of students in the texts and secondary sources, among them, the records of daily class, reports and projects developed, as well as reports of my pedagogical practice, as a researcher inserted in the investigative process. The experience developed, showed a writing school able to express nuances of human complexity, showing that learning is made in the action body, crossed by various forms of language and pointing to the relevance of a pedagogical work able to articulate the dialogue between the written and registrations body of the students, as subjects of learning